"A DIDACTIC APPROACH TO THE EFFECTIVE DEVELOPMENT OF CREATIVE COMPETENCIES IN FUTURE TEACHERS BASED ON FORESIGHT TECHNOLOGIES IN THE CONTEXT OF DIGITALIZATION." - Rahmonova Nilufar Najmiddin qizi (Western European Studies, 2026)
This article is intended for undergraduate students studying in the field of pedagogical higher education. It describes the pedagogical conditions, quality indicators, and information-didactic support for using innovative organizational-didactic forms of education in providing future teachers with methodological tools and knowledge related to creative pedagogical competence. The methodology for improving the creative competencies of future teachers based on Foresight technologies is highlighted through an innovative approach.
Keywords: Foresight; technique